New section and species in Talaromyces - Sun, Bing-Da (MycoKeys, 2020)
Talaromyces is a monophyletic genus containing seven sections. The number of species in Talaromyces grows rapidly due to reliable and complete sequence data contributed from all over the world. In this study agricultural soil samples from Fujiang, Guangdong, Jiangxi, Shandong, Tibet and Zhejiang provinces of China were collected and analyzed for fungal diversity. Based on a polyphasic approach including phylogenetic analysis of partial ITS, BenA, CaM and RPB2 gene sequences, macro- and micro-morphological analyses, six of them could not be assigned to any described species, and one cannot be assigned to any known sections. Morphological characters as well as their phylogenetic relationship with other Talaromyces species are presented for these putative new species. Penicillium resedanum is combined in Talaromyces section Subinflati as T. resedanus.